Culturally sensitive stepped care for adolescent refugees: efficacy and cost-utility of a multicentric randomized controlled trial: original contribution - Hoehne, Edgar; Böge, Kerem; Karnouk, Carine; Tschorn, Mira; Banaschewski, Tobias; Hoell, Andreas; Sukale, Thorsten; Plener, Paul; Schneider, Frank; Padberg, Frank; Hasan, Alkomiet; Rapp, Michael A.; et al. (European child & adolescent psychiatry, 2024)
Adolescent refugees and asylum seekers (ARAS) are highly vulnerable to mental health problems. Stepped care models (SCM) and culturally sensitive therapies offer promising treatment approaches to effectively provide necessary medical and psychological support. To our knowledge, we were the first to investigate whether a culturally sensitive SCM will reduce symptoms of depression and PTSD in ARAS more effectively and efficiently than treatment as usual (TAU). We conducted a multicentric, randomized, controlled and rater-blinded trial across Germany with ARAS between the ages of 14 to 21 years. Participants (N = 158) were stratified by their level of depressive symptom severity and then equally randomized to either SCM or TAU. Depending on their severity level, SCM participants were allocated to tailored interventions. Symptom changes were assessed for depression (PHQ) and PTSD (CATS) at four time points, with the primary end point at post-intervention after 12 weeks. Based on an intention-to-treat sample, we used a linear mixed model approach for the main statistical analyses. Further evaluations included cost-utility analyses, sensitivity analyses, follow-up-analyses, response and remission rates and subgroup analysis. We found a significant reduction of PHQ (d = 0.52) and CATS (d = 0.27) scores in both groups. However, there was no significant difference between SCM and TAU. Cost-utility analyses indicated that SCM generated greater cost-utility when measured as quality-adjusted life years compared to TAU. Subgroup analysis revealed different effects for the SCM interventions depending on the outcome measure. Although culturally sensitive, SCMs did not prove to be more effective in symptom change and represent a more cost-effective treatment alternative for mentally burdened ARAS. Our research contributes to the optimization of clinical productivity and the improvement of therapeutic care for ARAS. Disorder-specific interventions should be further investigated.
Online veröffentlicht: 16. März 2023
Gesehen am 26.02.2024